2006
DOI: 10.1111/j.1540-8167.2006.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Ablation During Pulmonary Vein Antrum Isolation Has No Adverse Impact on Left Atrial Function: An Echocardiography and Cine Computed Tomography Analysis

Abstract: Extensive ablation during PVAI does not cause deterioration in LA function, and may cause long-term improvement, especially in patients with higher AF burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 23 publications
(41 reference statements)
8
72
0
1
Order By: Relevance
“…1104,1105 A meta-analysis showed a significant decrease in LA volume but did not find significant changes in active LA function, including studies with persistent as well as PAF ablation procedures. 1106 However, because AF eliminates essentially all contractility of the LA, there is general agreement that restoration of sinus rhythm in patients with persistent AF improves atrial function if sinus rhythm is maintained.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…1104,1105 A meta-analysis showed a significant decrease in LA volume but did not find significant changes in active LA function, including studies with persistent as well as PAF ablation procedures. 1106 However, because AF eliminates essentially all contractility of the LA, there is general agreement that restoration of sinus rhythm in patients with persistent AF improves atrial function if sinus rhythm is maintained.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…Additionally, improvement in left atrial function has been noted after cardiac resynchronization for the treatment of heart failure (25). Atrial function is restored when the heart is returned to sinus rhythm, but whether atrial function post-ablation improves or declines compared to controls is controversial (26)(27)(28). The impact of scar formation, which has been shown to include around 30% of the LA endocardium, on contractility and conduction patterns is not fully understood (29).…”
Section: Other Clinical Implicationsmentioning
confidence: 99%
“…Reverse morphological remodelling of the left atria and improvement of left ventricular diastolic and systolic functions after restoration of sinus rhythm by ablation have been demonstrated in a study in patients with isolated AF 17 and other studies have reported similar findings. 23,[37][38][39][40] Although it is difficult to base assessment of long-term outcome on retrospective data, as techniques have changed since catheter ablation for AF was first introduced, available data are encouraging. In Bordeaux University Hospital, for example, the overall success rate of catheter ablation for AF remained quite stable at 62-63% between 1 year and 6 years of follow-up, 5% of patients moving from failure to success or vice versa (P. Jaïs, unpublished results).…”
Section: Is Atrial Fibrillation Ablation Ready For First-line Therapy?mentioning
confidence: 99%